Age-dependent court sentences and crime bunching: Empirical evidence from Swedish administrative data - Björn Tyrefors Hinnerich; Mårten Palme; Mikael Priks (Research Institute of Industrial Economics (IFN), 2017)
According to Swedish penal code, there is a "rebate" on all prison sentences before the 21st birthday. We exploit this age discontinuity to investigate how individuals respond to harsher punishments. We use a large Swedish dataset, including dates for all crimes which led to convictions for cohorts born during the period 1973-1993. We find evidence of "bunching" in the sense that more crimes were committed during the week prior to a 21st birthday, followed by a reduction in crime during the week after this birthday. We do not, however, find that harsher punishment reduces the crime rate permanently.
Keywords: D9; K4; 330; General deterrence; Prison; Sorting; Age thresholds